Two elephants - Anderson, Steven; Lebrun, Maxime (North Mankato, MN Cantata Learning, 2016)
Elephants on a spider web? How could it be? Count by twos as these jolly little elephants find out why a spider web might not be the best place to play. This hardcover library bound book comes with CD and online music access
English stories
1 2 13
NEW_ZTN_GN
Keywords: Children's songs -- Texts; Counting -- Songs and music -- Juvenile fictions; Elephants -- Songs and music -- Juvenile fiction